Left for dead : a mystery - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries., 2012)
When Santa Cruz county deputy sheriff Jose Reyes, one of Ali Reynolds's classmates from the Arizona Police Academy, is gunned down and left to die, he is at first assumed to be an innocent victim of the drug wars escalating across the border. But the crime scene investigation shows there's much more to it than that, and soon he and his pregnant wife, Teresa, are both under suspicion. Ali Reynolds owes Jose Reyes a debt of gratitude for the help he gave her years earlier. When she's summoned to his bedside at Mercy Medical Center in Tucson, it's impossible for Ali to turn away. Upon arriving at the hospital, Ali finds her good friend, Sister Anselm, is there as well, working as patient advocate on behalf of another seriously injured victim, an unidentified border crosser who was raped and savagely beaten. As more bodies pile up, Ali and Sister Anselm find themselves confronting the evil of the drug cartels across the border head-on, with no way of knowing who the next victim will be.